2015
DOI: 10.1111/pme.12678
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Lumbar Spine Radiofrequency Procedures in the Presence of Posterior Pedicle Screws: Technical Report of a Cadaver Study

Abstract: Titanium and stainless steel pedicle screws are capable of sustaining large increases in temperature when the radiofrequency probe comes in contact with the screw. These results are suggestive that pedicle screws could serve as a possible source of tissue heating and thermal injury during RFN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…With the increase in spinal instrumentation surgery interventional spine practitioners are likely to encounter patients with symptomatic zygapophysial joint pain [6]. However, hazards to the safe conduct of RFN arise in patients in whom pedicle screws have been used to facilitate fusion.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in spinal instrumentation surgery interventional spine practitioners are likely to encounter patients with symptomatic zygapophysial joint pain [6]. However, hazards to the safe conduct of RFN arise in patients in whom pedicle screws have been used to facilitate fusion.…”
Section: Introductionmentioning
confidence: 99%
“…One proposed risk of performing an RFN procedure in patients with posterior spinal instrumentation is the transmission of heat through the metallic hardware, causing thermal injury to surrounding structures. A cadaver study showed that it is possible for pedicle screws to heat significantly when in direct contact with an RF cannula (10). Additionally, a prospective study showed pedicle screws are capable of temperature increases (11).…”
Section: Methodsmentioning
confidence: 99%
“…Outcome measures were selected from potential serious complications/adverse events suggested in recently published papers (10,11). Chart abstraction criteria were developed by the research team based on these outcome measures (Table 1).…”
Section: E479mentioning
confidence: 99%
See 2 more Smart Citations